A new species of Maxillaria (Maxillariinae) from the northern Andes and a new synonym of Maxillaria floribunda - Pisso Florez, Gustavo Adolfo; Moreno Silva, Juan Sebastián; Harding, Patricia Ann 1951-; Baquero R., Luis E. (2024)
Maxillaria andina, a new orchid species from high-Andean ecosystems of southwestern Colombia and northern Ecuador, is described. The new species is distinguished by having long and narrowly lin-ear white sepals and petals with revolute margins, lip with mucronate epichile, and callus without hairs or trichomes. Distinguishing characters are provided to differentiate it from morphologically similar species, along with ecological and taxonomical notes. Additionally, Maxillaria sibundoyensis is synonymized with Maxillaria floribunda.
Maxillaria andina, una nueva especie de orquídea de ecosistemas altoandinos del suroccidente de Colombia y norte de Ecuador, es descrita. La nueva especie se distingue por presentar sépalos y pétalos blancos, largos y estrechamente lineales, con los márgenes revolutos, el labelo con un epiquilo mucronado y el callo sin pelos ni tricomas. Presentamos caracteres distintivos que diferencian a la nueva especie de sus especies morfológicamente similares, así como notas ecológicas y taxonómicas. Adicionalmente, Maxillaria sibundoyensis es sinonimizada con Maxillaria floribunda.
Keywords: ORQUIDEAS -- IDENTIFICACION -- COLOMBIA; ORQUIDEAS -- IDENTIFICACION -- ECUADOR; MAXILLARIA -- CLASIFICACIÓN